Teaching for deeper learning : tools to engage students in meaning making - McTighe, Jay; Silver, Harvey F. (ASCD, 2020)
"Jay McTighe and Harvey Silver offer a practical guide to teaching seven essential thinking skills that will equip students for success in school and beyond"--